Why does resource availability matter for honeybee colonies in spring? - Ulgezen, Z. N.; van Dooremalen, C.; van Langevelde, F. (Insectes sociaux, 2025)
Honeybees are essential pollinators that provide crucial ecosystem services across agricultural and natural landscapes. However, honeybee colonies, particularly in the Northern Hemisphere, are experiencing significant declines due to multiple stressors. While the parasitic mite Varroa destructor is a major threat, resource availability plays a vital role in colony health, vulnerability to stress, and social resilience. Despite its importance, the transitional period for colonies from late winter to early spring when resources are scarce and brood rearing demands high energy, is often overlooked in studies. Here, we propose that colonies are most vulnerable during this transitional period and emphasize the need for closer examination of the complex relationship between resource availability and colony status to better understand colony mortality that occur in this period. We argue that improving resource availability should be prioritized, not only for short-term colony survival but also for the long-term sustainability of honeybee populations.